Design of the National Gallery of Indonesia at the New Capital of Indonesia in East Kalimantan - Rafli Alfiano; Yuke Ardhiati (Catuspata Press, 2021)
Purpose: Coinciding with the decision of the President of the Republic of Indonesia to move the capital city of Indonesia to East Kalimantan, this paper was written for the purpose of ideally designing National Gallery of Indonesia (Galeri Nasional Indonesia or GNI) which is complete/integrated, representative, artistic, and has attractiveness as a tourist spot and recreation area. Research methods: Data collection in the design uses online data collection in order to obtain site data and also existing conditions based on the results of the Nagara Rimba Nusa competition. From this, data and analysis of the design are obtained which are then processed into a design concept. Findings: The design concept of the National Gallery of Indonesia in the new capital of Indonesia in East Kalimantan is combined with the design theme from Charles Jencks resulted in a building composition based on the analysis and also the previous concept. The composition of the gallery building mass resulting from the analysis and the theme of “multivalence” produces a unique building form with various philosophical meanings. Implications: The final result of the design process produces concepts, working drawings as well as the 3D rendering of the design.